Stability analysis of ultra-high and steep reinforced soil fills slopes based on strength reduction - Yucong Gao; Yue Zhao; Tianyuan Xu; Jinlong Xu (Archives of Civil Engineering, 2024)
The research focuses on solving the important problem of slope stability in the field of civil engineering. The study adopted an advanced strength double reduction coefficient method for slope stability analysis, which considers the different influence weights of cohesion and internal friction angle, and reduces them with different reduction coefficients to describe the stability of the slope. The simulation experiment results indicate that the attenuation degree of cohesion and internal friction angle affects slope stability. When the reduction coefficient of cohesion increases to 1.737 and the reduction coefficient of internal friction angle increases to 1.201, the slope is prone to instability and failure, and the safety factor of the calculated result is 1.493. Moreover, when the anti-slip pile is set in the middle of the slope (1/2), and the slope is in a critical state, the bending moment and shear force suffered by the anti-slip pile are both maximum, so the reinforcement effect is also the best.